Circulating α-Klotho Levels in Relation to Cardiovascular Diseases: A Mendelian Randomization Study - Sun, Xingang; Chen, Lu; He, Yuxian; Zheng, Liangrong (Frontiers in Endocrinology, 2022)
Background: Several studies have reported a protective role of circulating α-Klotho on cardiovascular diseases (CVD); however, the causality remains unclear. We aim to elucidate whether genetically predicted circulating α-Klotho levels were causally associated with the risk of coronary artery disease (CAD), atrial fibrillation (AF), heart failure (HF), stroke, ischemic stroke (IS), and IS subtypes. Methods: A two-sample Mendelian randomization (MR) study was designed, with 5 single-nucleotide polymorphisms associated with circulating α-Klotho levels utilized as instrumental variables. MR estimates on each CVD outcome derived from the fixed-effects inverse-variance weighted (IVW) approach in different data sources were combined by the fixed-effects meta-analysis approach, complemented by several sensitivity analyses including the simple median, the weighed median, MR-Egger regression, and MR-pleiotropy residual sum and outlier. Results: In the meta-analysis combining different data sources, suggestive inverse causal association of circulating α-Klotho concentrations with CAD [Odds ratio (OR), 0.97; 95% confidence interval (CI), 0.94, 1.00; P = 0.044] and significant inverse association of circulating α-Klotho concentrations with AF (OR, 0.96; 95% CI, 0.93, 0.99; P = 0.005) was observed. However, there was no causal association of α-Klotho with HF, any stroke, IS, or IS subtypes neither in different data sources nor in the meta-analysis. Complementary sensitivity analyses showed consistent and robust results in general. Conclusion: Evidence was found for a protective effect of circulating α-Klotho on the prevention of AF risk. However, no significant causal association between genetically predicted circulating α-Klotho levels and risk of CAD, HF, stroke, IS, or IS subtypes was found.